From industrial waste to functional ingredient: the potential of the pomegranate peel (INNOTEC, 2019)
During the industrial production of pomegranate juice, its peel is generated as a by-product. The aims of this work was to revalue these bu-product by green extraction of soluble antioxidants and recovery of insoluble fiber. Pomegranate by-product, once dried and ground was subjected to a water extraction process (65 ° C for 30 min), obtaining two fractions: one soluble and one insoluble. The insoluble fraction had a high fiber content (52.28 ± 2.99 g / 100 g) and the soluble fraction had a high total polyphenol content of 1049.98 ± 3.98 mg gallic acid / 100 g and an antioxidant capacity against ABTS radicals of 1486.57 ± 0.05 mol trolox / g. A jelly and a drink were formulated with the soluble fraction, while cookies and muffins were formulated with the insoluble fraction. All producto were formulated without sugar, and cookies and muffins so that they comply with the claim "source of fiber." Acceptability was evaluated by consumers (n = 100), with cookies and muffins being the most accepted (7.0 and 6.3 respectively). Pomegranate by-product were revalued sustainably and at a low cost, obtaining new functional ingredients, representing this an opportunity for the industry.
Keywords: pomegranate; by-products; antioxidant fiber; product development; sensory acceptability